2007
DOI: 10.1159/000106091
|View full text |Cite
|
Sign up to set email alerts
|

A Probiotic <i>Lactobacillus</i> Strain Can Acquire Vancomycin Resistance during Digestive Transit in Mice

Abstract: The present study demonstrates for the first time the transfer of vancomycin resistance (vanA cluster) from enterococci to a Lactobacillusacidophilus commercial strain. Transfers were observed in vitro, but also in vivo in the gut of mice (in the absence of antibiotic pressure) where transconjugants arose at relatively high frequencies and could persist in the digestive environment. Since transfer of vancomycin resistance genes might also take place in the human digestive tract, lactobacilli probiotics should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 56 publications
0
58
0
4
Order By: Relevance
“…Interspecies conjugative transfer of tetracycline and erythromycin resistance plasmids from lactobacilli has been demonstrated previously in vitro (Gevers et al, 2003a;Ouoba et al, 2008;Feld et al, 2008 Transfer has been demonstrated in the GIT of rodents, both gnotobiotic (Feld et al, 2008;Jacobsen et al, 2007;Morelli et al, 1988) and those having an indigenous gut microbiota (Feld et al, 2008;Jacobsen et al, 2007;Schlundt et al, 1994;McConnell et al, 1991;Gruzza et al, 1994;Igimi et al, 1996). In addition, the in vivo transfer of vancomycin resistance has recently been shown between enterococci and probiotic lactobacilli in gnotobiotic mice (Mater et al, 2008). Recent experiments of antibiotic resistance transferability in vivo were also conducted from L. plantarum to E. faecalis (Jacobsen et al, 2007).…”
Section: Evidence Of Potential Horizontal Gene Transfer Of Probiotic mentioning
confidence: 92%
“…Interspecies conjugative transfer of tetracycline and erythromycin resistance plasmids from lactobacilli has been demonstrated previously in vitro (Gevers et al, 2003a;Ouoba et al, 2008;Feld et al, 2008 Transfer has been demonstrated in the GIT of rodents, both gnotobiotic (Feld et al, 2008;Jacobsen et al, 2007;Morelli et al, 1988) and those having an indigenous gut microbiota (Feld et al, 2008;Jacobsen et al, 2007;Schlundt et al, 1994;McConnell et al, 1991;Gruzza et al, 1994;Igimi et al, 1996). In addition, the in vivo transfer of vancomycin resistance has recently been shown between enterococci and probiotic lactobacilli in gnotobiotic mice (Mater et al, 2008). Recent experiments of antibiotic resistance transferability in vivo were also conducted from L. plantarum to E. faecalis (Jacobsen et al, 2007).…”
Section: Evidence Of Potential Horizontal Gene Transfer Of Probiotic mentioning
confidence: 92%
“…The transfer of important antibiotic resistance genes across generations have also been demonstrated among lactobacilli and from lactobacilli to pathogens (Tannock, 1994). These reports have established probiotic bacteria as reservoirs of antibiotic resistant genes that can be transferred to pathogenic strains (Mater, 2008). This raises the question of antibiotic resistances among desired food borne bacteria such as starter and probiotic cultures.…”
Section: Issn: 2319-7706 Volume 7 Number 04 (2018)mentioning
confidence: 99%
“…Some serious concerns have been raised, supporting the hypothesis that typical probiotic genera can act as potential reservoirs of resistance for food or gut pathogens (Gueimonde et al, 2013;Schoster et al, 2014). Most of the available data on antibiotic resistance are available for lactobacilli, which have been proven to transfer genes to different gram-positive bacteria, but also acquire resistance genes from them (Mater et al, 2008). Due to their potential pathogenicity, antimicrobial resistance for clinically relevant antibiotics and in vitro evidence of enhancing adhesion of enteropathogens, enterococci also represent a serious safety issue and have, therefore, been avoided in studies considering potential probiotics in animals (Lund and Edlund, 2001;Rinkinen et al, 2003;Weese et al, 2004;Cebrian et al, 2012;Gueimonde et al, 2013).…”
Section: Quality and Safety Of Probiotic Preparationsmentioning
confidence: 99%